Hate Speech and Persecution: A Contextual Approach - Gordon, Gregory S. (2013)
Scholarly work on atrocity-speech law has focused almost exclusively on incitement to genocide. But case law has established liability for a different speech offense: persecution as a crime against humanity (CAH). The lack of scholarship regarding this crime is puzzling given a split between the International Criminal Tribunal for Rwanda and the International Criminal Tribunal for the former Yugoslavia on the issue of whether hate speech alone can serve as an actus reus for CAH-persecution. This Article fills the gap in the literature by analyzing the split between the two tribunals and concluding that hate speech alone may be the basis for CAH-persecution charges. First, this is consistent with precedent going as far back as the Nuremberg trials. Second, it takes into account the CAH requirement that the speech be uttered as part of a widespread or systematic attack against a civilian population. Third, the defendant must be aware that his speech is uttered as part of that attack. As a result, it is problematic to consider hate speech in a vacuum. Unlike incitement to genocide, an inchoate crime not necessarily involving speech and simultaneous mass violence, hate speech as persecution must be legally linked to contemporaneous violence in a context in which the marketplace of ideas is shut down and speech thus loses its democracy and self-actualization benefits. Thus, it should ordinarily satisfy the CAH-persecution actus reus requirement. Nevertheless, given the strictly verbal conduct, and possible impingements on quasi-legitimate freedom of expression, isolated or sporadic hate speech, as well as hate speech uttered as part of incipient, low-level, or geographically removed chapeau violence, may not qualify as the actus reus of CAH-persecution. The Article ultimately makes the point that context is crucial and case-by-case analysis should always be required